Financial, credit and budgetary support for the transfer of modern technologies for the modernization of the aerospace complex - Kosova, Tatiana; Raicheva, Larisa; Cherednichenko, Stanislav; Horbach, Yevhen; Chobitko, Vitalii (Eastern-European Journal of Enterprise Technologies, 2025)
The object of the study is the processes of financial, credit and budgetary support for the modernization of the aerospace complex based on the transfer of modern technologies. The problem of strategic innovation principles for the modernization of the aerospace complex is solved in order to preserve the scientific and technical potential of the state, strengthen the defense capability and increase the export potential of highly intelligent products. According to the results of statistical research, the achievements and problems of the modernization of the national economy and the aerospace complex of Ukraine based on the transfer of modern technologies during 2015–2023 were diagnosed. By industry, an increase in the volume of capital investments in cargo aerospace transport by 1050.9 million UAH, or by 435.7%. It is shown that the volume of capital investments in passenger aviation transport decreased by 962.1 million UAH, or by 74.78%. Structural changes are associated with a reduction in the share of passenger air transport from 84.21% to 20.07% against the background of an increase in the share of air cargo and space transport. By object, an increase in the share of software and databases from 26.7% to 62.44% was diagnosed. The features of the study are the use of a synergistic approach between the interaction of financial, credit, and budgetary instruments in the interests of ensuring cluster development of the aerospace industry. The scope of the results obtained is their implementation in the activities of international organizations, state and local governments, business entities, collective and individual investors to ensure the transfer of modern technologies for the modernization of the aerospace complex. The conditions for the practical use of the research results are the formation of a modern technology transfer infrastructure